Development of Zr(IV)—Doped polypyrrole/zirconium (IV) iodate composite for efficient removal of fluoride from water environment. (October 2017) - Rahman, Nafisur; Nasir, Mohd
Graphical abstract: Highlights: Zirconium (IV)-doped polypyrrole/zirconium (IV) iodate composite as a fluoride selective adsorbent was prepared and characterized. The material has a fluoride adsorption capacity of 183.5 mg g −1 . Ion exchange/ligand exchange controls the adsorption of fluoride. Adsorbent has been successfully applied to removal of fluoride from groundwater samples. Abstract: The present work reports the preparation of zirconium(IV)-doped polypyrrole/zirconium (IV) iodate composite for fluoride removal. The composite material was characterized by FTIR, XRD, TGA-DTA and SEM coupled with EDX. The effects of various experimental parameters such as pH, contact time, adsorbent dose and initial fluoride ion concentration on the fluoride removal were studied in batch mode and optimized for maximum removal of fluoride from water. The adsorption capacity was found to be 183.5 mg/g at pH 6.8. The adsorption isotherm data were well described by Freundlich isotherm model. The results of kinetic studies indicated that the experimental data fitted well with the pseudo-second-order kinetic model. The activation energy for adsorption of fluoride on the adsorbent was found to be 37.04 kJ/mol. The adsorbent has been successfully applied to remove fluoride from groundwater by column method.